Efforts to Improve Public Speaking Skills Through Speech Practice Methods for Elementary School Students 2 Sumberingin - Syafira Putri Ramadhani (JOSAR (Journal of Students Academic Research), 2025)
Public speaking is a crucial skill that should be developed from an early age. At State Elementary School 2 Sumberingin, this skill is underdeveloped, evident in the low participation of students during presentations or class speaking activities. This community service activity aimed to enhance students' public speaking abilities through a gradual and structured speech training method. The activity involved speech training encompassing the basic theory of public speaking, speaking practice, and student performance evaluation. A participatory approach was employed, actively involving students and teachers over two weeks. The results showed a significant improvement in student confidence, their ability to write speeches, and their skills in expressively delivering speeches in public. The activity received a positive response from the school and is expected to become a regular program.